2012
DOI: 10.1371/journal.pone.0031808
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil Induced Intestinal Mucositis via Nuclear Factor-κB Activation by Transcriptomic Analysis and In Vivo Bioluminescence Imaging

Abstract: 5-Fluorouracil (5-FU) is a commonly used drug for the treatment of malignant cancers. However, approximately 80% of patients undergoing 5-FU treatment suffer from gastrointestinal mucositis. The aim of this report was to identify the drug target for the 5-FU-induced intestinal mucositis. 5-FU-induced intestinal mucositis was established by intraperitoneally administering mice with 100 mg/kg 5-FU. Network analysis of gene expression profile and bioluminescent imaging were applied to identify the critical molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
107
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(120 citation statements)
references
References 40 publications
(50 reference statements)
13
107
0
Order By: Relevance
“…Caspase-3 is the major downstream effector in apoptosis. Some researchers reported that 5 -Flurouracil induces DNA damage and the production of reactive oxygen species, deteriorates the metabolism in progenitor cells and causes inhibition of mitosis and rises of apoptosis [2,3,6,27]. Other scientists [5,23,24] found that the toxicity of chemotherapeutic agents as 5-FU decreases proliferation of cells of mucosa, also impairment of their cellular renewal or regeneration and thus lead to significant decrease of PCNA immunostaining expression of the mucosal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 is the major downstream effector in apoptosis. Some researchers reported that 5 -Flurouracil induces DNA damage and the production of reactive oxygen species, deteriorates the metabolism in progenitor cells and causes inhibition of mitosis and rises of apoptosis [2,3,6,27]. Other scientists [5,23,24] found that the toxicity of chemotherapeutic agents as 5-FU decreases proliferation of cells of mucosa, also impairment of their cellular renewal or regeneration and thus lead to significant decrease of PCNA immunostaining expression of the mucosal cells.…”
Section: Discussionmentioning
confidence: 99%
“…5-FU is one of the anti-cancer drugs widely utilized in the treatment of CRC in clinical practice (6). However, continuous use of 5-FU usually has severe toxic effects, particularly intestinal mucositis (12), resulting in discontinuation of cancer chemotherapy and impairment of the quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, normal cells, tissues and their functions are inevitably injured by 5-FU, which disrupts the balance of the body's self-regulatory system (4,5). The major side effects of 5-FU include intestinal mucositis, myelosuppression and immunosuppression (6). It has been reported that ~80% of cancer patients who have received 5-FU treatment displayed clinical manifestations of intestinal mucositis, such as severe diarrhea, mal-absorption, vomiting and bleeding (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, reactive oxygen species (ROS) are formed, starting downstream biological events. Nuclear factor kappa B (NFκB), cyclooxygenase-2 (COX-2) as well as pro-inflammatory cytokines like interleukin-6 (IL-6), interleukin-1β (IL-1β) and tumour-necrosis factor (TNF) have been suggested to play a key role in the development of GIM (17)(18)(19)(20). These overlapping steps are thought to be largely driven by the activation of NFκB, subsequently promoting key pro-inflammatory cytokines.…”
Section: Pathobiology Of Gimmentioning
confidence: 99%